PENGARUH TERAPI AKTIVITAS KELOMPOK TERHADAP KEMAMPUAN PASIEN MENGONTROL HALUSINASI DI RSJIWA MENUR SURABAYA: PENGARUH TERAPI AKTIVITAS KELOMPOK TERHADAP KEMAMPUAN PASIEN MENGONTROL HALUSINASI DI RSJIWA MENUR SURABAYA - Nikmah, Khoerun (WELL BEING, 2017)
Hallucinations are perception problems where the client perceives something that doesn’t exist and mental disorder is a healthy emotional condition, physiology and social that seen from satisfaction interpersonal, effective attitude and coping. Purpose of this research is to know the effect of group of activity therapy to control ability of the patients to their hallucinations. In this research, writer used Quasi Experiment research design by using pre-post test design and group control design with mann-whitney test by using SPSS 16 program. Most of the respondents as many as 16 and quota sapling technique where the sample is the hallucinations patients in Rumah Sakit Jiwa Menur Surabaya. Research result showed that respondent’s ability before they are given group of activity therapy was poor as many as 6 respondents (75%), those who weren’t given group of activity therapy as many as 7 respondents (87,5%), and respondent’s ability after given group of activity therapy, most of them had good respond as many as 2 respondents (25%) whereas those who weren’t given group of activity therapy only 1 respondents (12,5%). TAK effect to patient’s ability to control hallucinations got score ρ = 0,014, where ρ< 0,05 so that H1 is accepted that means there’s different between experimental group and control and also there’s effect before and after given TAK. This data showed that group of activity therapy influenced the ability of patients to control hallucinations